1998
DOI: 10.1128/jcm.36.6.1621-1624.1998
|View full text |Cite
|
Sign up to set email alerts
|

Use of PCR for Diagnosis of Post-Kala-Azar Dermal Leishmaniasis

Abstract: Microscopy and PCR were compared for use in the diagnosis of post-kala-azar dermal leishmaniasis (PKDL) in 63 patients. Aspirates of lymph nodes (samples from 52 patients), skin (23 samples), and bone marrow (18 samples) were used. For 11 patients lymph node aspiration could be repeated 6 months after they recovered from PKDL. During active PKDL, PCR was positive for 42 of 52 (80.8%) lymph node aspirates and 19 of 23 (82.7%) skin aspirates, whereas microscopy was positive for only 9 of 52 (17.3%) lymph node as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…10 In another study by our group, 30% of smears were positive by microscopy and 83% by PCR. 11 These findings show that PKDL should be considered a distinct pathological entity which is the result of dissemination of parasites to the skin and the host's developing immune response to parasite antigens after successful treatment for kala-azar.…”
Section: Discussionmentioning
confidence: 99%
“…10 In another study by our group, 30% of smears were positive by microscopy and 83% by PCR. 11 These findings show that PKDL should be considered a distinct pathological entity which is the result of dissemination of parasites to the skin and the host's developing immune response to parasite antigens after successful treatment for kala-azar.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown that the immunochromatographic strips impregnated with k39 antigen provided a simple and reliable diagnostic test for PKDL. The sensitivity of detection was higher than that in procedures requiring high technical expertise such as immunohistochemistry 5 or PCR 7 . The test appeared to be suitable for use in endemic as well as non‐endemic regions of the country.…”
Section: Discussionmentioning
confidence: 92%
“…As a result, PKDL is easily confused with a number of dermatological conditions, of which leprosy is the most important 4 . In recent years, improved sensitivity and specificity for the diagnosis of PKDL has been reported by use of anti‐ L. donovani monoclonal antibodies, Western blotting and polymerase chain reaction (PCR) 5–7 …”
mentioning
confidence: 99%
“…Using an immunoperoxidase technique and anti‐ L. donovani monoclonal antibody, they achieved high sensitivity with microscopy. Using slit skin smears of PKDL patients, Leishmania DNA was detected in 19 of 23 samples by PCR, whereas with microscopy parasites were only found in seven ( Osman et al . 1998a ).…”
Section: Diagnosismentioning
confidence: 99%
“… Endemic and epidemic areas of visceral and cutaneous leishmaniasis in the Sudan (adapted from Osman 1998 ). …”
Section: Introductionmentioning
confidence: 99%